Determinación de la edad según características morfológicas de los incisivos de ovinos desde el nacimiento hasta los 5,5 años - Luengo L., Juan; Godoy Z., Luciano; Aros I., Carlos; García D., Guillermo; Gómez R., Lautaro (Avances en Ciencias Veterinarias, 1991)
A study in Suffolk Down and Precocious Merino sheep was done from birth to five and half, years old. The morphologic characteristics of the incisors considerad were: eruption, wearing and fall of temporary incisors, eruption, wearing and complete wearing of permanents incisors. The results of the incisors morphological characteristics studied in both breeds not showed significant differences. Rule is propesed for age determinación in regard to sheep carcasses classification. Key words: age, incisors, ovines. Palabras claves: edad, incisivos, ovinos.